2021
DOI: 10.1680/jencm.19.00039
|View full text |Cite
|
Sign up to set email alerts
|

Validation of simulated wave energy converter responses to focused waves

Abstract: Cite this article van Rij J, Yu YH and Tran TT (2021) Validation of simulated wave energy converter responses to focused waves.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…In the NewWave Theory approach, the average shape of the highest wave with a specified exceedance probability is produced for a given sea state [26]. The theory has been used extensively to study WEC behaviour in equivalent extreme waves both numerically and experimentally, see, e.g., [5,6,11,14,16,27]. In Table 4, the equivalent focused wave profiles can be found.…”
Section: Equivalent Regular Wavesmentioning
confidence: 99%
See 2 more Smart Citations
“…In the NewWave Theory approach, the average shape of the highest wave with a specified exceedance probability is produced for a given sea state [26]. The theory has been used extensively to study WEC behaviour in equivalent extreme waves both numerically and experimentally, see, e.g., [5,6,11,14,16,27]. In Table 4, the equivalent focused wave profiles can be found.…”
Section: Equivalent Regular Wavesmentioning
confidence: 99%
“…When comparing the CFD models for the regular and focused waves, they found that the former showed up to 34% difference from the experimental design load response, whereas the latter produced a result within 17% of the experimental data. In [14], a WEC-Sim model was compared with a STAR-CCM+ CFD model for a focused wave obtained using NewWave theory, and the overall responses predicted by the two models compared well, and were on average within 5% from each other. This is in contrast to the results of [18], where the dynamics predicted by a high-fidelity CFD method gave a better agreement with experimental data than linear-based models.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For a deeper analysis in extreme wave conditions, high-fidelity computational fluid dynamics (CFD) codes are widely employed to provide accurate evaluation of the dynamics of WEC mechanisms by capturing viscous effects, wave breaking, slamming, overtopping, and large amplitude motions. The most widely used CFD-based approach is the incompressible two-phase Reynolds averaged Navier-Stokes simulations [8], implemented in several recent studies [9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a weakly nonlinear formulation is often used to account for the nonlinear buoyancy and Froude-Krylov forces, induced by the instantaneous free surface elevation and body position. As presented in [12], [13] WEC-Sim was applied in a study as part of the Collaborative Computational Project in Wave Structure Interaction 2 (CCP-WSI) Blind Test Series 2 for a hemisphericalbottomed cylinder and a truncated cylinder with a cylindrical moon pool under series of focused waves.…”
mentioning
confidence: 99%